Early postoperative feeding following surgery for upper gastrointestinal cancer: A systematic review. Issue 1 (12th July 2021) - Carmichael, Lauren; Rocca, Rose; Laing, Erin; Ashford, Phoebe; Collins, Jesse; Jackson, Luke; McPherson, Lauren; Pendergast, Brydie; Kiss, Nicole
Abstract: Nutrition post major upper gastrointestinal (UGI) cancer surgery is a significant consideration known to affect postoperative recovery and the ability to tolerate adjuvant treatment. This systematic review assessed the effect of early oral feeding (EOF), compared to traditional timing of oral feeding, following major surgery for UGI cancer on postoperative complications, postoperative length of hospital stay (LOS), nutritional status and quality of life (QOL). The literature was searched up to March 9th 2020 using CINHAL, PubMed, MEDLINE, Embase, Scopus and Web of Science databases. Quality assessment was completed using the Academy of Nutrition and Dietetics quality criteria checklist. Fifteen articles were included, consisting of seven randomised controlled trials, six cohort studies and two non‐randomised trials, with a total of 2517 participants. The type and timing of EOF varied considerably across studies with limited reporting of energy and protein intakes from oral or enteral feeding. Fourteen studies assessed postoperative complications of which 13 reported no difference between EOF and standard care. Fourteen studies assessed postoperative LOS and of these, 13 reported a reduced length of stay in the EOF group. Four of 15 studies assessing nutritional status found no difference between groups. Three of 15 studies assessed QOL with inconsistent findings. This review found EOF reduced postoperative LOS and did not increase postoperative complications. However, the optimal timing for the introduction of EOF could not be established. Furthermore, the type of EOF varied considerably making comparison across studies challenging and demonstrates a need for internationally standardised definitions. Abstract : Summary of systematic review findings.